Strategies for Recruitment of Stem Cells to Treat Myocardial Infarction - Shafiq, Muhammad; Lee, Sang-Hoon; Jung, Youngmee; Hyun Kim, Soo (Current Pharmaceutical Design, 2015)
Heart failure is one of the most prominent causes of morbidity and mortality worldwide. According to the World Health Organization, coronary artery disease and myocardial infarction (MI) are responsible for 29% of deaths worldwide. MI results in obstruction of the blood supply to the heart and scar formation, and causes substantial death of cardiomyocytes in the infarct zone followed by an inflammatory response. Current treatment methodologies of MI and heart failure include organ transplantation, coronary artery bypass grafting, ventricular remodeling, cardiomyoplasty, and cellular therapy. Each of these methodologies has associated risks and benefits. Cellular cardiomyoplasty is a viable option to decrease the fibrosis of infarct scars, adverse post-ischemic remodeling, and improve heart function. However, the low rate of cell survival, shortage of cell sources and donors, tumorigenesis, and ethical issues hamper full exploitation of cell therapy for MI treatment. Consequently, the mobilization and recruitment of endogenous stem/progenitor cells from bone marrow, peripheral circulation, and cardiac tissues has immense potential through harnessing the host’s own reparative capacities that result from interplay among cytokines, chemokines, and adhesion molecules. Therapeutic treatments to enhance the mobilization and homing of stem cells are under development. In this review, we present state-of-the-art approaches that are being pursued for stem cell mobilization and recruitment to regenerate infarcted myocardium. Potential therapeutic interventions and delivery strategies are discussed in detail.
Keywords: angiogenesis